An Investigation of the Knowledge of Infection Control Practices Held by Healthcare Professionals - Gazi R. Rahman; Amiya Bhaumik (Wolters Kluwer Medknow Publications, 2024)
Background: Healthcare-associated infections (HAIs), arising from inadequate hygiene practices, significantly increase morbidity and mortality rates in hospitalized patients. Materials and Methods: This descriptive study involved 350 healthcare workers from private hospitals in Wuhan, China. Participants responded to a questionnaire with close-ended questions, distributed physically and via email. Data were analyzed using SPSS version 25.0. Results: The analysis indicated a gap in healthcare workers' knowledge of infection control, affecting hospital hygiene standards. About 60% of respondents hold a diploma or higher qualification. Conclusion: The findings underscore the importance of targeted training and educational initiatives in infection control procedures. A significant factor in hospitals' inadequate hygiene practices is the gap in staff training and knowledge.